PENGARUH PENGEMBANGAN KARIR, KEPUASAN GAJI, DAN BEBAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN GEN Z DI PT SUNWOO GARMENT INDONESIA - Putri, Windy Annisa; Waskito, Jati (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effect of workload, salary satisfaction, and career development on turnover intention among Generation Z employees at PT Sunwoo Garment Indonesia. The study adopts a quantitative research design and applies a survey technique by administering structured questionnaires to 150 participants who were chosen based on purposive sampling criteria. The collected data were analyzed using multiple linear regression analysis, classical assumption tests, and instrument testing. Hypothesis testing was conducted using F-tests and t-tests with a significance level of 0.05, supported by the coefficient of determination (R²). The results indicate that career development has a negative but insignificant effect on turnover intention, suggesting that this factor is not a primary consideration for Generation Z employees in deciding whether to remain with or leave the company. In contrast, salary satisfaction has a significant and negative effect on turnover intention, indicating that higher salary satisfaction reduces employees’ intention to leave. In addition, workload has a significant effect on turnover intention, where a higher workload tends to increase employees’ intention to leave the organization. Overall, salary satisfaction and workload are more dominant factors influencing turnover intention among Generation Z employees than career development.